FRACTIONAL PROPERTY OWNERSHIP BY USING BLOCKCHAIN ALGORITHM - Gan, Jia Wei (Universiti Malaysia Sarawak (UNIMAS), 2019)
Fractional property ownership has been a trend for property investors because of its flexibility that allows investors to invest fractionally in not only one property, but several properties. Fractional ownership is being defined as a percentage ownership in an asset. Fractional ownership shares are the assets sold to the property investors who share the benefits of the asset such as usage rights, income sharing and priority access. With fractional ownership, the value of the shares increases with the assets increases in value. In other words, fractional ownership is a form of collaborative consumption where overall cost of a property is split among a group of property owners. By doing so, we implemented ERC20 token as smart contract to fractionalise the a single token into shares. Nonetheless, there are also increasingly more perpetrators tried to penetrate the investment details of the investors in order to tamper with the information for their personal gain. Therefore, to safeguard the investment/transaction details of the investors, a secure cryptosystem is required to safeguard the sensitive transaction data. In our project, we are going to develop a property website where it provides fractional property investment for the investors. Furthermore, blockchain technology will be implemented in order to safeguard the investment/transaction details. Therefore, the transaction details are meddle-proof and immutable. This ensures the accountability, confidentiality, and integrity of the transaction details. At the same time, we have taken full advantage of the key characteristics of Ethereum blockchain technology to not only ensure that upmost security is provided to the transaction details, but also to solve the issues of heavy cost and bottleneck induced by heavy traffic of transactions, to provide anonymity for the investors, and to verify and track the transactions effectively. In the near future, we are going to integrate the module in a property website to allow fractional property investment for the investors in real world.